The proof of this can be get with a slight modification. It can be prove that every bounded is convergent, If (an) is an increasing and bounded sequence, then limn → ∞an = sup{an:n∈N} and if (an) is a decreasing and bounded sequence, then limn→∞an = inf{an:n∈N}.
Step-by-step explanation:
-2x - 5y = 16___(1)
2x - 3y = -16___(2)
(1) + (2) ==> -2x -5y = 16
(+) <u>2x -3y = -16</u>
-8y = 0
y = 0/-8
y = 0
y=0 in (1)
(1)---> -2x-5y =16
-2x - 5(0) = 16
-2x - 0 = 16
-2x = 16
x = 16/-2
x = -8
x = -8 , y = 0
-5x + 2y = 11__(1) ; -3x + 4y = -13___(2)
multiply eqn(1) with 2
2 × (1) : -10x + 4y = 22___(3)
(3) - (2) :. -10x + 4y = 22
(-) <u>-3x </u><u>+</u><u> </u><u>4</u><u>y</u><u> </u><u>=</u><u> </u><u>-</u><u>1</u><u>3</u>
-7x = 35
x = 35/-7
x = -5
x=-5 in (1)
(1) : -5x + 2y = 11
-5(-5) + 2y = 11
25 + 2y = 11
2y = 11 - 25
2y = -14
y = -14/2
y = -7
x = -5 , y = -7
Answer:
ASA
Step-by-step explanation:
In the 2 triangles
∠J = ∠L
side OJ = side IL
∠O = ∠I
The triangles are congruent by the angle/side/angle (ASA ) postulate
12:25 is not equivalent to the rest
What do you mean by this question?